Performance as the basis of goal-directed behavior - Serdakova, K.G.; Ionkina, E.G.; Kolchin, A.V.; Bohan, E.A.; Melnikov, D.S. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate the effectiveness of students entering a specialized university faculty, taking into account their motivation for future professional activities. Methods and structure of the study. The study was carried out on the basis of the results of the competitive selection of 251 students in the period from 1996 to 2000. To select the best of the most motivated students for future activities, students of the 2nd and 3rd courses of specialized universities of the Russian Federation with high educational results were admitted to competitive tests. Results and conclusions. The dominant learning motivation, reflecting the intellectual preparation of the student, his success in mastering the fundamental disciplines is the leading one in the effectiveness of admission to a specialized research faculty. At the same time, the student's creative abilities are an important, however, independent characteristic of the individual. Thus, emotionally colored motivation is the basis for the effectiveness of a behavioral act.